(untitled) (Asian Journal of Pharmaceutics (AJP), 2026)
Against the backdrop of modern medical progress, messenger RNA (mRNA) holds a bright future, yet its therapeutic potential highly relies on effective delivery. This review, “Smart Carriers for Smarter Cures,” explores the innovative use of stimuli-responsive nanomaterials as protective and precise carriers for mRNA. We first understand the innate challenges of mRNA transport, including its susceptibility to enzymatic degradation and its difficulty in crossing cell membranes independently. The core of our discussion focuses on how these smart carriers support biological and external triggers for highly targeted drug release. Further, we study how they respond to a variety of cues, such as shifts in pH and redox potential within the body, as well as external stimuli like light. This focused approach reduces unintended effects and increases therapeutic capability. We also try and understand the variety of carrier types, such as lipid nanoparticles and polymeric systems. We deeply discuss the mechanisms that they use for cargo delivery too. In a nutshell, this review highlights the main impact of these technologies across various applications, like the important development of advanced mRNA vaccines and customized cancer treatments. By identifying the important delivery hurdles, these intelligent nanocarriers are recreating a new era in nanomedicine and gene therapy where our future is full of more effective and safer treatments.